EFFECTS OF MUSIC ON HUMAN HEALTH - Dilbar Jabborova; Yusufboyeva Mohirabonu (Social science and innovation, 2023)
The article describes the effect of music on the functions of many physical systems, as well as on the nervous system. It is discussed how musical genres can have positive and negative effects on organs, as well as the impact of musical instruments on human health. The article provides research by scientists and public figures on the influence of music on our body and the use of music as a therapeutic agent.